1931 Mich. Pub. Acts 671, § 237 - (:unkn) unknown (My University, 1931)
The Michigan Penal Code, ch. 37, §237: Any person under the influence of intoxicating liquor or any exhilarating or stupefying drug who shall carry, have in possession or under control, or use in any manner or discharge any fire-arm within this state, shall be guilty of a misdemeanor.
Keywords: POSSESSION - DANGEROUS PERSONS